Cheios do Espírito Santo, para servir. Ênfases pneumatológicas do Diaconado - Maçaneiro, Marcial; Rigoni, Miguel (Revista Eclesiástica Brasileira, 2020)
Em vista de um diaconado missionário, que responda eclesialmente aos sinais dos tempos, este artigo busca explicitar as enfases pneumatologicas que este ministério comporta, a luz da Palavra de Deus e do magistério da Igreja, em vista da evangelização. A abordagem é dinâmica, em atenção aos apelos e buscas pastorais que tocam o diaconado, na voz dos pontífices – de Paulo VI (Evangelii Nuntiandi e Ad pascendum) até Francisco (Evangelii Gaudium) – e com exame das Conclusões de Puebla e Aparecida. Todo esse acervo é lido em chave pneumatológica, a partir da narrativa lucana da eleição dos Sete Diáconos, cuja expressão “cheios do Espírito” (At 6,3: plereis pneumatos) é assumida como critério articulador da reflexão. Ao concluir, sao apresentadas as perspectivas para o diaconado em cinco âmbitos de ação do Pneuma: a caridade, a verdade, a unidade, a missão e a Criação. Abstract: In view of a missionary diaconate, which respond ecclesially to the signs of the times, this article seeks to explain the pneumatological emphases that this ministry implies, in the light of the Word of God and the Church’s magisterium, in view of evangelization. The approach is dynamic, taking into account the pastoral appeals and searches that touch the diaconate, in the voice of the pontiffs – from Paul VI (Evangelii Nuntiandi and Ad pascendum) to Francis (Evangelii Gaudium) –and with an examination of the Conclusions of Puebla and Aparecida Conferences. This set of documents is read in a pneumatological key, based on the Lucan narrative of the election of the Seven Deacons, whose expression “filled with the Spirit” (At 6.3: plereis pneumatos) is assumed as an articulating criterion for reflection. In conclusion, the prospects for the diaconate are presented in five areas of action of Pneuma: charity, truth, unity, mission, and Creation. Keywords: Diaconate; Pentecost; Pneumatology; Church’s Magisterium; Mission.